PENGARUH DISIPLIN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA PADA KARYAWAN CV. X - Muhammad Ridwan; Suherman Suherman; Solikhah Solikhah (Yayasan Education and Social Center, 2023)
The purpose of this study is to determine whether work discipline and have an effect on job satisfaction at CV X’s employee. This study used a sample of 64 employees of CV X. This study uses quantitative approach with descriptive and explanatory analysis method. Data was collected by distributing survey questionnaires to 64 employees of CV X. The data analysis method used for hypothesis test in this study is using the SEM (Structural Equation Modeling) Method. The results of this study shows that work discipline has a positive and significant effect on employee job satisfaction at CV X and the compensation has a positive and significant effect on employee job satisfaction at CV X